Enhancing students' numeracy literacy in human heredity material through a brain-based learning model - Waliyyatu Azzahra; Sariwulan Diana; Eni Nuraeni (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2024)
In this digital era, data and information in biology are increasingly presented in quantitative form that must be processed and interpreted. To deal with this, students' numeracy literacy becomes essential to train. This study aims to reveal an increase in students' numeracy literacy by implementing the brain-based learning model. This study used a quasi-experimental method with a pretest-posttest non-equivalent group design. The sample consisted of 28 students in the experimental class and 30 students in the control class who had been selected by random sampling. The instruments used were question sheets with various types, such as the Minimum Competency Assessment (MCA) questions. The findings of this study indicate that the experimental class has a higher N-Gain Score, which is 0.71 with high criteria, while in the control class, it is 0.60 with a moderate category. The better N-Gain Score can also be seen from each numeracy literacy indicator's analysis. This indicates that the brain-based learning model improves students' numeracy literacy more effectively. Based on these findings, further research can conduct a long-term study of applying the brain-based learning model to students' numeracy literacy to understand the sustainability of the improvements.Abstrak. Di era digital ini, data dan informasi dalam ilmu biologi semakin banyak disajikan dalam bentuk kuantitatif yang harus diproses dan diinterpretasikan. Dalam rangka menghadapi hal tersebut, literasi numerasi siswa menjadi hal yang penting untuk dilatih. Tujuan penelitian ini adalah untuk mengungkap adanya peningkatan literasi numerasi siswa melalui implementasi Model Brain Based Learning. Penelitian ini menggunakan metode eksperimen semu dengan desain pretest posttest non-equivalent group design. Sampel terdiri dari 28 siswa pada kelas eksperimen dan 30 orang siswa kelas kontrol yang telah dipilih secara random sampling. Instrumen yang digunakan adalah lembar soal dengan berbagai tipe seperti pada soal Asesmen Kompetensi Minimum (AKM). Temuan penelitian ini menunjukkan bahwa kelas eksperimen memiliki N-Gain Score yang lebih tinggi, yaitu sebesar 0.71 dengan kriteria tinggi, sedangkan pada kelas kontrol sebesar 0.60 dengan kategori sedang. Perolehan N-Gain Score yang lebih baik juga terlihat dari analisis setiap indikator literasi numerasi yang diteliti. Hal ini menandakan bahwa model Brain Based Learning lebih efektif dalam meningkatkan literasi numerasi siswa. Berdasarkan temuan tersebut, penelitian berikutnya dapat melakukan analisis jangka panjang dari penerapan Model Brain Based Learning terhadap literasi numerasi siswa untuk memahami keberlanjutan peningkatan yang dicapai.